Strategies for implementing Sustainability in Quality Improvement (SusQI) education: educator perspectives - Kathleen Leedham-Green; Ayoma Ratnappuli; Frances Mortimer; Alice Clack; Victoria Stanford; Siobhan Parslow-Williams (BMJ Open Quality)
The climate and ecological emergencies represent a significant threat to health, and yet healthcare is a major contributor to environmental degradation. Sustainability in Quality Improvement (SusQI) is a framework that enables healthcare professionals to improve how good health is achieved and healthcare delivered in line with social, economic and environmental sustainability goals. SusQI education provides healthcare learners with the knowledge and practical skills for sustainable clinical transformation.We interviewed 11 SusQI course leads at 10 educational sites in the UK and Ireland, exploring educator perspectives on how SusQI can be successfully implemented in diverse health educational contexts. Our aim was to identify what works, in which contexts and why. We thematically analysed the interviews and tabulated case study details.We identified four interlinked themes: choosing SusQI, getting it into the curriculum, making it work and embedding it. Each of these stages was influenced by factors related to the educators themselves, their students and their institution, as well as specific educational or curricular factors. The most successful implementations demonstrated synergistic benefits for both learners and institutions, engendering self-sustaining communities of practice.Strong institutional commitment, distributed expertise and opportunities for supported project work emerge as key success factors. Together, these fostered self-sustaining virtuous cycles of stakeholder engagement, transformative educational impacts and progress towards sustainable clinical practice.